Impact of Learning Management Systems and Digital Skills on TPACK Development Among Pre-service Mathematics Teachers - Muh Fitrah; Caly Setiawan; Widihastuti Widihastuti; Anastasia Sofroniou; Nur Azizatur Rahmawati; Arina Arina; Sri Ratna Sari; Iskandar Iskandar (Qubahan Academic Journal, 2025)
The technological era has significantly impacted the quality of mathematics education. In reality, the frequency of technology usage in the classroom is minimal, and teachers continue to face challenges when utilizing learning management systems (LMS). Therefore, the purpose of this study is to identify the impact of LMS on the development of technological pedagogical content knowledge (TPACK) and digital skills of pre-service mathematics teachers. This mixed-methods study, employing an exploratory approach, involved 76 pre-service mathematics teachers (22 males, 54 females). Data was collected through questionnaires and interviews and subsequently compiled using Microsoft Excel and saved in CSV format. The data were then analyzed using Jamovi software version 2.4.8.0. Findings show that digital skills significantly influence TPACK development (β = 0.63, p < 0.001), more so than LMS usage (β = 0.49, p < 0.001), with a combined explanatory power of 65% (R² = 0.65). Higher digital skills improve pre-service teachers' ability to integrate technology into pedagogy and content. Additionally, final-year pre-service teachers show greater competencies. Male pre-service teachers generally exhibit higher digital skills than females (p < 0.001), influencing their capacity to effectively use digital tools in teaching. The strong correlation between digital skills and LMS usage (Spearman’s ρ = 0.86) underscores the need for structured digital competency development in teacher education. These findings emphasize the importance of fostering digital literacy and technology-integrated practicum experiences in mathematics instruction. Universities and school administrators should implement targeted training programs to enhance LMS utilization and help pre-service teachers develop strong TPACK competencies.